The Lysosome Origin of Biosilica Machinery in the Demospongiae Model Petrosia ficiformis (Poiret, 1789) - Pozzolini, Marina; Mikšík, Ivan; Ghignone, Stefano; Oliveri, Caterina; Tassara, Eleonora; Giovine, Marco (Frontiers in Marine Science, 2022)
The silicification mechanism in sponges is a biologically controlled process where the complex and amazing shape of spicules is the result of the hierarchical assembly of silicon particles to form a composite structure with organic compounds, mainly constituted by proteins. In this work, using an integrated approach of transcriptomic and proteomic analysis, we describe the protein content of sponge spicules in the marine demosponge Petrosia ficiformis (Poiret, 1789). Proteins from spicules were obtained via an ammonium fluoride extraction procedure to remove the inorganic silica followed by SDS-PAGE electrophoresis. The resulting data of LC-MS/MS analysis of the extracted SDS-PAGE bands were then processed with the MASCOT software to search against a database consisting of transcripts and predicted proteins of P. ficiformis. The results revealed a very heterogeneous group of 21 proteins, including silicatein beta, different isoforms of cathepsins, proteins with strong homologies with enzymes like sulphatases, glycosidases, lipid-related proteins, phosphatases, and some others with unknown function. Most of the proteins found here have structures and domains attributable to lysosomes enzymes and for this reason it could be related to these cellular structures the evolutionary origin of the biosilica machinery in sponges.